Perception of Women, Political Marriages and The Role of Women in State Administration During the Era of Crusader States - Altınay, Ramazan; Dağdeviren, Habibe Ceren (Journal of History Culture and Art Research, 2021)
This study examines political marriages, the perception of women and the role of women in state administration in the Crusader States’ era. The Crusades, one of the largest military operations of the Middle Ages, is a period of about two hundred years that confronted the Western Christians and the Eastern Muslims, starting in 1096 and lasting until the expulsion of Latin Christians from Akka in the East in 1291 and covering eight major military expeditions. In the introduction section of the research, after examining the historical process of the Crusades, it was tried to examine the perception of women during the period of the expeditions and the approach of women against the expeditions. Later, the influence of marriages with noblewomen in the Crusader states (the Crusader Count of Urfa (1098-1144), the Principality of Antioch (1098-1268), the Kingdom of Jerusalem (1099-1291) and the Count of Tripoli (1109-1289) on politics was discussed. In this part of the research, numerous examples of the influence of marriages with noblewomen on politics are given. Based on the examples given, it was concluded that the rulers of the Crusader states attached importance to such factors as concluding agreements or fighting in the interests of order to be able to maintain, strengthen and expand the political organization they had created, as well as to relations established through marriage. It has been determined that kinship relations established through marriages with noblewomen or daughters of local rulers sometimes expand their areas of dominance and even provide alliances against threatening forces, and sometimes the continuation of states occurs thanks to these marriages. The study also concludes that, despite the negative woman perception during the Middle Ages, noblewomen took an active role in politics and in establishing political relations in this period. In this aspect, the study also provides a general perspective on understanding the roles of women throughout history especially in the political field based on the examples from the period of Crusader states.